ADSORPTION OF Cu(II) and Zn(II) IONS on PROTONATED ZSM-5 ZEOLITE - Tresna Umi Culsum, Neng
Cu(II) and Zn(II) are an important metal that has various widely used in industrial processes. Both are used in textile industry, electroplating, metallurgy, electronics, paper and paint. That process produces wastewater and will accumulate in enviroment. Cu and Zn are an essential micronutrient for human. But it would cause health problem such as canceer at a very high concentration, Since they are toxic and mutagenic. The maximum limit of Zn and Cu metal in the water are 5 mg/L and 2 mg/L respectively.Therefore, effective methods required to reduce the concentration of Cu(II) and Zn(II) metal in the environment. One of the method that can be conducted is adsorption using zeolite as adsorbent. Zeolites are porous material containing pores and cavities at the molecular dimensions. Zeolite ZSM5 has some good features, such as pore structure, surface area, selective separation ability, thermal stability, and it has a silanol (SiOH), AlOH, and OH ( SiOHAl) group at the surface that bind with heavy metal ion. This research aim to study the adsorption process of Cu(II) and Zn(II) ions on the structure of zeolite ZSM-5 by determining the optimum conditions, isotherms, kinetics and thermodynamics of adsorption and compare the adsorption capacity of the Cu(II) and Zn(II) ions using protonated zeolite ZSM-5 and unprotonated ZSM-5. Study was conducted in two stages: (1) protonation and characterization of zeolit ZSM-5 (2) adsorption ion Cu(II) and Zn(II) using a ZSM-5 and determining the optimum adsorption conditions, contact time, pH, adsorbent mass, temperature, selectivity and adsorption-desorption. XRD and SEM characterizations confirmed the structure of ZSM-5 with a hexagonal prismatic morphology. The results show that the optimum adsorption of Cu(II) ions was achieved at the time of 20 minutes and the optimum adsorption of metal ions Zn(II) was achieved at the time of 10 minutes. Langmuir and Freundlich isotherm was used to interpret the adsorption data from ZSM-5. Adsorption process of ion Cu(II) and Zn(II) on zeolite ZSM-5 followed the Langmuir isotherm with qm 12.164 mg/g and 2.092 mg/g. The kinetic studies of